The Storied South : Voices of Writers and Artists - Ferris, William R. (Book collections on Project MUSE., 2013)
The Storied South features the voices--by turn searching and honest, coy and scathing--of twenty-six of the most luminous artists and thinkers in the American cultural firmament, from Eudora Welty, Pete Seeger, and Alice Walker to William Eggleston, Bobby Rush, and C. Vann Woodward. Masterfully drawn from one-on-one interviews conducted by renowned folklorist William Ferris over the past forty years, the book reveals how storytelling is viscerally tied to southern identity and how the work of these southern or southern-inspired creators has shaped the way Americans think and talk about the Sou.